PENGAWASAN PETUGAS PERTAMANAN DI DINAS LINGKUNGAN HIDUP DAN PERTAMANAN KABUPATEN SUMEDANG - Dadan Setia Nugraha (JRPA - Journal of Regional Public Administration, 2019)
This study aims to analyze the problems of supervision in the Sumedang Regency Department of Environment and Forestry Department, inhibiting factors in conducting surveillance, as well as efforts to overcome obstacles in conducting supervision in the Sumedang District Department of Environment and Forestry Department. The method used in the preparation of this research report is a qualitative research method (Naturalistic Setting) with descriptive type. The sampling technique used is purposive sampling. With research informants: Head of Waste and Parks Management Division, Head of RTH Maintenance Section, Parks and Cemeteries, Staff I Section RTH Maintenance, Parks and Cemeteries, and Staff II RTH Maintenance Section, Parks and Cemeteries. Data collection techniques through secondary data collection techniques such as library studies and documentation. In analyzing the data used the Miles and Huberman models with the steps: Data reduction, Data presentation, Conclution Drawing / Verification, and Triangulation. Based on the research, it is found that in conducting supervision, determining standards is important because it is a guideline in measuring the level of effectiveness. The absence of guidelines clearly becomes an obstacle in the implementation of an activity, especially regarding activities within a government agency. There is an effort to minimize the absence of reference standards, namely by persuasive approaches to employees.